Public-elite gap on European integration: the missing link between discourses among citizens and elites in Serbia. Issue 6 (17th August 2020) - Kortenska, Elitsa; Steunenberg, Bernard; Sircar, Indraneel
ABSTRACT: This article explores the relationship between elite and citizen discourses on European integration. We argue that imperfections in cue-making and cue-taking lead to a gap between elite and citizen discourses, especially in societies experiencing major changes. To investigate this, we use newly collected data from Serbia shortly after the delayed start of accession negotiations in 2014. Using vignettes for different citizen discourses, we coded statements collected from major Serbian newspapers. The analysis shows that citizen discourses found in previous research are all represented in the media. We also find that approximately one fourth of media content does not fit any of the citizen discourses in Serbia. This gap confirms our hypothesis and demonstrates that elite 'communicative' discourses are not well linked to citizen discourses, leading to politically important imperfections.